Desain Desain Perancangan Alat Deteksi Kondisi Ruangan Untuk Penderita Sleep Apnea Berbasis Esp32 - Feriyanto, Yanuar; Ariyanto, Arif Setia Sandi; Triwibowo, Deny Nugroho (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Sleep apnea is a serious sleep disorder characterized by repeated interruptions of breathing during sleep. This condition can significantly reduce sleep quality and have an impact on the health of individuals experiencing sleep apnea. In this condition, it can affect sleep disturbances that may lead to oxygen deficiency, high blood pressure, heart disease, and even other complications. Sleep disorders are also often not recognized by sufferers, resulting in delayed diagnosis and treatment. Environmental factors during sleep, including temperature, humidity, air quality, lighting, and noise, greatly influence the room conditions of people with sleep apnea. Therefore, a device is needed that can directly detect room conditions to keep the sleeping environment ideal. This research develops a device design to detect room conditions using an ESP32 microcontroller; this system is equipped with a DHT22 sensor to measure temperature and humidity, an MQ-135 sensor to monitor air quality, a BH1750 sensor to measure light intensity, and a KY037 sensor to detect sound. All data obtained from these sensors are then transmitted via Wi-Fi connection to the Blynk application, allowing users to monitor this information directly through their smartphones. This device design not only provides information on room conditions but can also be an effective solution to help sleep apnea sufferers maintain their sleep quality. Thus, this tool can present relevant environmental data and make it easier for users to monitor room conditions.